Behaviour of RC Beams Retrofitted With Combined Jute and Glass Fibre Woven Fabrics in Flexure - Amitpal (My University, 2019)
Strengthening/retrofitting of existing structures now days has become a common practice in construction industry. It is also known that many structures in present world are currently in need of up gradation due to many factors such as increase in traffic volume, inadequate design procedures, increase in loads, structures exceeding their design life and many other environmental factors such as earthquake, floods, etc. Therefore, effective methods are required for structural strengthening of existing structures as well as structural retrofitting of preloaded structural elements. Out of many retrofitting methods, fabric jacketing is one of the most popular and easy method of retrofitting now a days. This study deals with the method of fabric jacketing as a retrofitting technique. Fabric jacketing is found to be suitable technique of retrofitting due to its light weight, easy application and good tensile strength. It has been found from the previous studies that natural fibres alone, when used as a wrapping material in retrofitting of beams are incapable of withstanding high loads and stresses. In this study jute fibre as a natural and glass fibre as a synthetic woven fabric is used as a retrofitting material. A total of fourteen beams were casted in this study, out of which two beams were control beam and remaining twelve beams were retrofitted with suitable layering technique. Two types of wrapping schemes and three types of layering system was adopted in this study which includes Side Wrapping and three side UWrapping with Type-1 layering, Type-2 layering and Type-3 layering systems in each wrapping scheme. Type-1 layering system consisted of “one glass-one jute” layer, Type-2 layering system consisted of “two glass-one jute layer” and Type-3 layering system consisted of “two glass-two jute layers” bonded to the beams alternatively. Firstly, two control beams were tested under UTM to their failure load and the ultimate failure load was noted. Then all the remaining twelve beams were preloaded to 60% of the ultimate failure load. Six beams, in group of two beams, for each wrapping scheme were retrofitted and were tested under UTM to find their ultimate failure load and study their load deflection behaviour. It was found that beams wrapped with three side U-Wrapping schemes showed a better load deflection behaviour and higher ultimate failure load than the beams wrapped with Side Wrap scheme. Out of three types of layering system, Type-3 layering system which consisted of two glass-two jute fabric layers in alternate manner showed more failure load as compared to other two layering systems.
Keywords: retrofitting; flexure; jute; glass; FRP